An introduction to perovskites for solar cells and their characterisation. (November 2022) - Bello, Suleiman; Urwick, Adam; Bastianini, Francesco; Nedoma, Alisyn J.; Dunbar, Alan
Abstract: Perovskite solar cells are one of the most active areas of renewable energy research at present. The primary research objectives are to improve their optoelectronic properties and long-term stability in different environments. In this paper, we discuss the working principles of hybrid perovskite photovoltaics and compare them to the competing photovoltaic technologies of inorganic and organic photovoltaics. The current challenges that hinder the commercialisation of perovskite solar cells are then discussed. This is followed by a description of perovskite material properties and some characterisation techniques commonly used to assess perovskite properties, fabrication processes including the use of antisolvents, and degradation mechanisms. We intend that this work should serve as a beginner's guide to the study of perovskite solar cells.